Neutralization of the neuromuscular inhibition of venom and taipoxin from the taipan (Oxyuranus scutellatus) by F(ab′)2 and whole IgG antivenoms. (22nd January 2016) - Herrera, María; de Cássia de O. Collaço, Rita; Villalta, Mauren; Segura, Álvaro; Vargas, Mariángela; Wright, Christine E.; Paiva, Owen K.; Matainaho, Teatulohi; Jensen, Simon D.; León, Guillermo; Williams, David J.; Rodrigues-Simioni, Léa; et al.
Highlights: The neuromuscular junction blockade by taipan venom and taipoxin was studied. Whole IgG and F(ab′)2 antivenoms were compared for their neutralizing activity. Antivenoms inhibited the blockade when incubated with venom or toxin before injection. When added after toxin or venom, neutralization depended on the time interval. No differences between antivenoms were observed in a mouse in vivo model. Abstract: The neuromuscular junction activity of Oxyuranus scutellatus venom and its presynaptic neurotoxin, taipoxin, and their neutralization by two antivenoms were examined in mouse phrenic nerve-diaphragm preparations. The action of taipoxin was also studied at 21 °C. The efficacy of the antivenoms was also assessed in an in vivo mouse model. Both antivenoms were effective in neutralizing the neuromuscular blocking activity in preincubation-type experiments. In experiments involving independent addition of venom and antivenoms, neutralization depended on the time interval between venom addition and antivenom application. When taipoxin was incubated for 5, 10 or 20 min at 21 °C, and antivenom added and temperature increased to 37 °C, neutralization was achieved only when the toxin was incubated for 5 or 10 min. The neutralization by the two antivenoms in an in vivo model showed that both whole IgG and F(ab′)2 antivenoms were effective in neutralizing lethality. Our findings highlight the very rapid action of taipan venom at the nerve terminal, and the poor capacity of antivenoms to revert neurotoxicity as the time interval between venom or taipoxin application and antivenom addition increased. Additionally the disparity between molecular masses of the active substances of the two antivenoms did not result in differences in neutralization.